Ecosystem services in agricultural and urban landscapes - Wratten, Stephen D.; Sandhu, Harpinder; Cullen, Ross, 1948-; Costanza, Robert (Chichester, West Sussex, UK ; Hoboken, NJ, USA : Wiley-Blackwell, 2012)
Ecosystem services are the resources and processes supplied by natural ecosystems which benefit humankind (for example, pollination of crops by insects, or water filtration by wetlands). They underpin life on earth, provide major inputs to many economic sectors and support our lifestyles. Agricultural and urban areas are by far the largest users of ecosystems and their services and (for the first time) this book explores the role that ecosystem services play in these managed environments. The book also explores methods of evaluating ecosystem services, and discusses how these services can b.
Ecosystem services in farmland and cities / Harpinder Sandhu and Steve Wratten -- Ecological processes, functions and ecosystem services : inextricable linkages between wetlands and agricultural systems / Onil Banerjee, Neville D. Crossman and Rudolf S. de Groot -- Key ideas and concepts from economics for understanding the roles and value of ecosystem services / Pamela Kaval and Ramesh Baskaran -- Viticulture can be modified to provide multiple ecosystem services / Sofia Orre-Gordon, Marco Jacometti, Jean Tompkins and Steve Wratten -- Aquaculture and ecosystem services : reframing the environmental and social debate / Corinne Baulcomb -- Urban landscapes and ecosystem services / Jürgen Breuste, Dagmar Haase and Thomas Elmqvist -- Scale-dependent ecosystem service / Yangjian Zhang, Claus Holzapfel and Xiaoyong Yuan -- Experimental assessment of ecosystem services in agriculture / Harpinder Sandhu, John Porter and Steve Wratten -- Towards multifunctional agricultural landscapes for the Upper Midwest region of the USA / Nicholas Jordan and Keith Douglass Warner -- Supply chain management and the delivery of ecosystems services in manufacturing / Mary Haropoulou, Clive Smallman and Jack Radford -- Market-based instruments and ecosystem services : opportunity and experience to date / Stuart M. Whitten and Anthea Coggan -- Epilogue : equitable and sustainable systems / Steve Wratten, Harpinder Sandhu, Ross Cullen and Robert Costanza.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Ecosystem services; Ecosystem management; Ecology -- Economic aspects; BUSINESS & ECONOMICS -- Development -- Sustainable Development; NATURE -- Environmental Conservation & Protection; Ecology -- Economic aspects; Ecosystem management; Ecosystem services; Ecology -- Economic aspects; Ecosystem management; Ecosystem services; Electronic books; Electronic books